2016
DOI: 10.17269/cjph.107.5336
|View full text |Cite
|
Sign up to set email alerts
|

Black-White health inequalities in Canada at the intersection of gender and immigration

Abstract: OBJECTIVES: Intersectionality theory proposes that each combination of social categories derived from gender, race and nationality, such as immigrant White man or native-born Black woman, is associated with unique social experiences. We tested the potential of intersectionality theory for explicating racial inequalities in Canada by investigating whether Black-White health inequalities are conditioned by gender and immigrant status in a synergistic way. METHODS:Our dataset comprised 10 cycles (2001)(2002)(2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…However, racial identities both singular and hybrid are imbued with social significance in Canadian society which means that they can be causally implicated in the production of health inequalities for social reasons. Consistent with previous research (Veenstra 2009;Chiu et al 2010;Liu et al 2013;Veenstra and Patterson 2015;Ramraj et al 2016;Patterson and Veenstra 2016;Veenstra and Patterson 2016), I find that, compared to White Canadians, Black Canadians are relatively likely to report hypertension after controlling for age and immigrant status. A small portion of this risk is attributable to differences in income.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, racial identities both singular and hybrid are imbued with social significance in Canadian society which means that they can be causally implicated in the production of health inequalities for social reasons. Consistent with previous research (Veenstra 2009;Chiu et al 2010;Liu et al 2013;Veenstra and Patterson 2015;Ramraj et al 2016;Patterson and Veenstra 2016;Veenstra and Patterson 2016), I find that, compared to White Canadians, Black Canadians are relatively likely to report hypertension after controlling for age and immigrant status. A small portion of this risk is attributable to differences in income.…”
Section: Discussionsupporting
confidence: 89%
“…For example, researchers have documented that, after controlling for age and immigrant status, Black Canadians are more likely than White Canadians to report hypertension and diabetes (Veenstra 2009;Chiu et al 2010;Liu et al 2010;Veenstra and Patterson 2015;Ramraj et al 2016;Patterson and Veenstra 2016;Veenstra and Patterson 2016) and native-born Black Canadians are more likely than native-born White Canadians to report poor self-rated health (Veenstra and Patterson 2015). Conversely, Black women are less likely than White women to report poor selfrated mental health and Black Canadians have lower agestandardized mortality rates than White Canadians (Wilkins et al 2008;Pinault et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, compared with the United States, blacks in Canada had relatively higher education, income, and employment (42). Nonetheless, recent studies have shown that black-white disparities still persist in Canada in regards to income and education (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the impacts of class, gender, race, migration and sexual orientation in Canada have been investigated (43,44), as has those of gender, sexual orientation and race in the United States (45,46), and of class, gender and regional context in Spain (47). Common to these studies, however, is that they adopt a categorical approach focused on between-group differences in average risk, without assessing individual heterogeneity and thus potentially allowing for a complementary anti-categorical stance.…”
Section: Self-rated Healthmentioning
confidence: 99%